Response of Some Landrace Rice (Oryza sativa L.) Cultivars to Applied Nitrogen in Lowland Ecosystem (The Agriculturists, 2018)
An experiment was conducted to determine the effects of nitrogen (N) fertilization on growth and yield of some landrace rice (Oryza sativa L.) cultivars in lowland ecosystem. Three popular landrace rice cultivars: Rajashail, Kutiagni and Sadamota were treated with five times of N application viz. (i) two split applications of prilled urea (PU) at 10 days after transplanting (DAT) and before panicle initiation (PI) stage, (ii) deep placement of urea super granule (DPUSG) at 10 DAT, (iii) DPUSG before PI stage, (iv) PU application before PI stage and (v) control. The results showed that the landrace rice cultivar Kutiagni had the highest number of tillers under PU, while  Rajashail gave the highest number of tillers under DPUSG applied before PI stage. Further, Kutiagni produced higher amount of dry matter under two splits of PU, while Rajashail produced higher amount of dry matter under DPUSG applied before PI stage. However, application of PU before PI stage significantly increased leaf area index in all the three landraces. The varieties responded to applied N and produced the highest yield in Kutiagni. The DPUSG at 10 DAT increased straw yield but failed to increase grain yield even over control. The DPUSG before PI stage significantly increased rice yield and economic return. The yield of rice in DPUSG applied before PI stage was comparable to two splits of PU and top dressing of PU before PI stage. Compared to control (2.93 t ha-1), yield increase was 26% in Kutiagni (3.70 t ha-1) under DPUSG before PI stage. These results suggest that Kutiagni was more responsive to added N and this cultivar could be cultivated with DPUSG at PI stage.The Agriculturists 2018; 16(1) 01-12